2008
DOI: 10.1002/ijc.23673
|View full text |Cite
|
Sign up to set email alerts
|

CHFR expression is preferentially impaired in smoking‐related squamous cell carcinoma of the lung, and the diminished expression significantly harms outcomes

Abstract: Loss of tumor suppressors and activation of oncogenes lead to carcinogenesis. Abnormal expression of CHFR, a novel checkpoint gene, or of Aurora kinases, key regulators of mitosis, has been detected in a variety of solid tumors. Recently, CHFR has been revealed to ensure chromosomal stability by controlling the expression level of Aurora-A in vitro. However, the frequency of aberrant expression of these proteins and the association with clinicopathologic parameters remain poorly defined in nonsmall-cell lung c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
24
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 44 publications
3
24
1
Order By: Relevance
“…In contrast, we demonstrated that reduced CHFR protein expression is associated with squamous cell carcinoma of NSCLC, smoking habit and tumor differentiation. 22 In the present study, we showed that EGFR gene mutation of clinical NSCLC samples was significantly related to resistance to PTX in opposition to CHFR methylation. In opposition to our results, a recent clinical study showed that the response rate of paclitaxel plus carboplatin treatment in the EGFR mutation-positive subgroup is higher than that in the EGFR wild-type subgroup.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…In contrast, we demonstrated that reduced CHFR protein expression is associated with squamous cell carcinoma of NSCLC, smoking habit and tumor differentiation. 22 In the present study, we showed that EGFR gene mutation of clinical NSCLC samples was significantly related to resistance to PTX in opposition to CHFR methylation. In opposition to our results, a recent clinical study showed that the response rate of paclitaxel plus carboplatin treatment in the EGFR mutation-positive subgroup is higher than that in the EGFR wild-type subgroup.…”
Section: Discussionmentioning
confidence: 49%
“…Sodium bisulfite conversion of genomic DNA was performed using the EZ DNA Methylation Kit (Zymo Research, Orange, CA), as described previously. 22,31 Methylation-specific PCR (MSP) was carried out with the following oligonucleotide primers, which were designed to be specific to either the methylated or unmethylated DNA sequence of the CHFR gene after sodium bisulfite conversion as described above. The methylated DNA-specific primers were MF (5'-ATA TAA TAT GGC GTC GAT C-3') and MR (5'-TCA ACT AAT CCG CGA AAC G-3').…”
mentioning
confidence: 99%
“…In contrast to the study of Tang et al (30), the prognostic significance of AURKA expression in the present study appears to hold true for both histological subtypes. There is a lack of consensus on this issue, with previous studies debating on the prognostic significance of AURKA in SqCCL (17,18). Furthermore, perimembrane immunohistochemical staining was demonstrated to be a marked predictor of poor prognosis in patients with SqCCL, but not in patients with AdC (16), whereas microarray data analysis demonstrated that AURKA mRNA overexpression is associated with poor prognosis in patients with AdC, but not in patients with SqCCL (30).…”
Section: Discussionmentioning
confidence: 99%
“…AURKA serves a central role in recruiting other mitotic spindle members (5). A number of previous studies conducted in lung cancer have investigated the prognostic value of various of the aforementioned genes, including TPX2 (15), AURKA (16)(17)(18) and AURKB (18)(19)(20)(21); however, the prognostic value of AURKA and AURKB remains a matter of debate. No information on the potential prognostic significance in human NSCLC has yet been provided for DLGAP5, CKAP5 or TTK.…”
Section: Introductionmentioning
confidence: 99%
“…7 CHFR is a ubiquitin ligase of Plk1 and Aurora-A. It functions as a mitotic checkpoint by delaying entry into metaphase in response to mitotic stress induced by nocodazole or paclitaxel.…”
mentioning
confidence: 99%